1996
DOI: 10.1159/000188904
|View full text |Cite
|
Sign up to set email alerts
|

HDL Subtractions Distribution in Renal Transplant Recipients: Lack of Evidence of a Reduction of HDL<sub>2</sub> Particles

Abstract: Since the high rate of cardiovascular disease in renal transplant recipients, alterations of lipoprotein profile in such patients were extensively evaluated, but the HDL subclass profile was not completely clarified. Renal transplant recipients usually show normal to high plasma levels of HDL cholesterol, even if some investigations suggested a persistence of low HDL2 levels: this was not useful in terms of cardiovascular protection. We designed this study in order to evaluate HDL subfractions distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In RTR, the main lipid alteration is hypercholesterolemia [87,90], while hypertriglyceridemia is less pronounced. HDL cholesterol levels has been found normal or high in this category of subjects; HDL subfractions are variable since some researchers have demonstrated low levels of HDL2 [91] while others failed to show any decrease of HDL2 particles [92]. Lp(a) are only slightly increased when kidney function improves [15], but its metabolism is not completely known.…”
Section: Renal Transplantationmentioning
confidence: 86%
“…In RTR, the main lipid alteration is hypercholesterolemia [87,90], while hypertriglyceridemia is less pronounced. HDL cholesterol levels has been found normal or high in this category of subjects; HDL subfractions are variable since some researchers have demonstrated low levels of HDL2 [91] while others failed to show any decrease of HDL2 particles [92]. Lp(a) are only slightly increased when kidney function improves [15], but its metabolism is not completely known.…”
Section: Renal Transplantationmentioning
confidence: 86%
“…This abnormality is not corrected by hemodialysis and persists also after kidney transplantation [ 27 ]. It has also been demonstrated that renal transplant recipients presented significantly lower levels of HDL3a and HDL3b and, in males, higher levels of HDL2b than controls [ 28 ]. Our results confirm these data.…”
Section: Discussionmentioning
confidence: 99%
“…As major metabolic risk factor for CHD, HDL-C has recently been qualified in a prospective study as the best lipid-related predictor of CHD in RTX [1]. However, very heterogeneous HDL-C levels have been reported in RTX, and the mechanisms underlying the marked individual differences are poorly understood [4, 5, 21]. Genetic family studies suggest that 40–60% of the variation of HDL-C between individuals is determined by genetic factors [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, unexpected results have been reported concerning serum HDL-C levels in RTX patients. Indeed, although decreased HDL-C levels have been reported [2], most studies have found normal or slighly elevated HDL-C levels in RTX, a paradoxical finding in a patient population characterized by a high prevalence of hyperlipidemia and accelerated atherosclerosis [3, 4, 5]. These conflicting data on HDL-C levels and their relationship with CHD in RTX suggest poorly understood and complex interactions between the immunosuppressive therapy and the metabolic and/or genetic factors determining HDL-C levels in this patient population.…”
Section: Introductionmentioning
confidence: 99%